Evolution of speech perception in patients with ossified cochlea and short array cochlear implant - Fraga, Guilherme Adam (2023)
Purpose. To report the speech perception of users of cochlear implants (CI) with short array, indicated as rehabilitation in patients with severe to profound deafness, especially when there is cochlear ossification. In these cases, with reduced intracochlear patency, total insertion becomes more difficult, requiring the use of this type of electrode (15 mm). Few studies have been published to evaluate auditory performance in these patients, presenting controversial audiological results. Methods. A retrospective analysis of medical records of patients who underwent surgery for cochlear implantation with short electrode, between 2009 and 2020, at the Hospital for Rehabilitation of Craniofacial Anomalies, University of São Paulo (HRAC-USP) was carried out. Results. There was performance evolution in the speech perception tests in the data analysis. Meningitis and congenital hearing loss were the main indications for CI in the sample. Conclusion. CI with a short lead is an alternative in the management of patients with a history of cochlear ossification and severe or profound sensorineural hearing loss. Significance. To demonstrate the evolution of speech perception tests with short array cochlear implant in patients with or without ossified cochlea and its characteristics for application in clinical practice.